Exploring the Impact of Bank-Specific Internal Factors on the Profitability: A Study of Banking Sector of Nepal - Dongol, Padam (Journal of Kathmandu BernHardt College, 2025)
The aim of this study is to investigate the impact of bank-specific internal factors on the profitability of the banks. The study, which employed an explanatory research technique, used secondary data from major sample merger commercial banks' annual reports for fiscal years 2014 to 2022. The population consists of 20 scheduled banks, with a sample of five merged banks selected purposefully. Bank size, liquidity ratio, dividend payout ratio, capital adequacy ratio and non-performing loans ratio are the five independent variables that the study uses to analyze the association between Return on asset, the dependent variable. The study used descriptive statistics, multiple regression models, and MS Excel for data analysis. The findings indicate that both BS and NPLR have a noteworthy detrimental impact on ROA, whereas LR has a considerable beneficial effect. However, the results revealed no statistical significance for CAR and DPR. The study concludes that among the internal factors analyzed, LR is the most influential factor on bank profitability. These findings provide valuable insights for regulators, bank management, and other stakeholders, highlighting areas for potential performance improvement. The inclusion of macroeconomic aspects with the potential to impact the profitability of Nepalese banks should be further examined.